SISTEM INFORMASI PENGEMBANGAN KARIR MAHASISWA UNIVERSITAS INDO GLOBAL MANDIRI - Agustina Heryati; Erduandi Erduandi (Jurnal Informatika Global, 2018)
Currently the University of IGM is required to produce graduates who have competence and high competitiveness. One benchmark of success lies in how quickly graduates are absorbed in the world of work. Based on the results of tracer study in 2014, the amount of alumni absorbed in the world of work, in accordance with educational background = 25%, the number of alumni who work not in accordance with educational background = 45% and the number of alumni who have not worked / no news = 30 %. The results of the calculation is not a proud thing, the cause of the problem is most of IGM University graduates are not ready for work, lack of information about job vacancies, IGM Training Center role is not maximal and management of tracer study is less effective. From these problems arise the idea of building applications for Student Career Development at the University of IGM.Application Career Development Student is a guidance application for Student self-development. This app is website based. Forecasting technique to predict the quality of Student by using artificial neural network backpropagation. Five pengguna roles are Student, alumni, stakeholder, IGM training center and study program contribute to provide uptodate information. The application will manage the data to be submitted to the pengguna Career development application used from the first semester to the end, the application will read the needs of students for the achievement of competence.Therefore through this application can be a trager for Students to help prepare themselves before entering the world of work.Keywords: Website application, Information System, Student career